The Alignment, Interest and Influence Matrix (AIIM) guidance note - Mendizabal, Enrique (ODI/RAPID, 2010)
In 2007, on the eve of a workshop to introduce a new version of the RA PID approach to DFID policy teams, Enrique Mendizabal and Ben Ramaling am created the Alignment, Interest and Influence Matrix (AIIM), a stak eholder analysis tool that not only helps to identify key stakeholders , but also suggests a possible course of action towards them.